2017
DOI: 10.1101/141820
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic Identification of a Common Collagen Disease in Puerto Ricans via Identity-by-Descent Mapping in a Health System

Abstract: 48Achieving confidence in the causality of a disease locus is a complex task that often 49 requires supporting data from both statistical genetics and clinical genomics. Here we 50 describe a combined approach to identify and characterize a genetic disorder that 51 leverages distantly related patients in a health system and population-scale mapping. 52We utilize genomic data to uncover components of distant pedigrees, in the absence of 53 recorded pedigree information, in the multi-ethnic BioMe biobank in New … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
37
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 106 publications
0
37
0
Order By: Relevance
“…We hypothesize that the Puerto Rican patients carry homozygous mutations due to identity by descent due to a founder mutation arising in Puerto Rico. This is supported byBelbin et al, 2017, who identified five patients of Puerto Rican ancestry with homozygous mutations and concordance of IBD haplotype with the mutations. This article was also able to determine a carrier rate of 1:51 for Puerto Ricans individuals.…”
mentioning
confidence: 64%
See 4 more Smart Citations
“…We hypothesize that the Puerto Rican patients carry homozygous mutations due to identity by descent due to a founder mutation arising in Puerto Rico. This is supported byBelbin et al, 2017, who identified five patients of Puerto Rican ancestry with homozygous mutations and concordance of IBD haplotype with the mutations. This article was also able to determine a carrier rate of 1:51 for Puerto Ricans individuals.…”
mentioning
confidence: 64%
“…When these surgeries have been performed, the affected joint tends to redislocate eventually.Eleven of the 14 patients with a molecular confirmation of Steel syndrome had the same homozygous c.2089G>C p.Gly697Arg mutation. Of these 11, 10 were Puerto Rican(Belbin et al, 2017;Gonzaga- Jauregui et al, 2015, our three patients) while one was from the United Arab Emirates(Gariballa et al, 2016). The patient from the United Arab Emirates had consanguineous parents (first cousins).…”
mentioning
confidence: 97%
See 3 more Smart Citations